Process for the preparation of a cationic dyeable nylon 6 resin and fibers
Patent Information
- Application Number
- CN202611414206.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
常规尼龙6纤维通常采用酸性染料染色,但酸性染色体系存在不足:(1) 染色色泽饱和度受限,难以获得高鲜艳度的亮色或深色体系;(2) 耐日晒牢度不佳,长期日照条件下易发生褪色或色变;(3) 为获得深染效果常需额外补充多氨基单体,易造成织物手感和稳定性劣化
1.平面刚性与极性匹配:呋喃基团为含氧杂芳结构,极性高于苯环,与尼龙6酰胺链段偶极相互作用更强;
Smart Images

Figure CN122898978A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of synthetic fiber materials and their modified dyeing technology, specifically to a method for preparing cationic dyeable nylon 6 resin and fiber, and more particularly to a technical solution that introduces sodium sulfonate copolymer structural units and furan end groups into the PA6 molecular chain, so that the resulting fiber has cationic dyeability, color fastness, mechanical properties and melt spinning processing properties. Background Technology
[0002] Nylon 6 fiber is widely used in the textile and industrial fields due to its good strength, abrasion resistance and resilience. Conventional nylon 6 fiber is usually dyed with acid dyes, but the acid dyeing system has the following shortcomings: (1) The color saturation of the dyeing is limited, and it is difficult to obtain bright or dark colors with high vividness; (2) The light fastness is poor, and it is easy to fade or change color under long-term sunlight; (3) In order to obtain a deep dyeing effect, it is often necessary to add extra polyamino monomers, which can easily cause the fabric's hand feel and stability to deteriorate.
[0003] To improve the color vibrancy and lightfastness of nylon 6 fibers, existing techniques have attempted to introduce anionic sites such as sulfonates into the nylon 6 chain segments, enabling them to bind with cationic dyes and thus improve dye uptake and color performance. However, the introduction of sulfonate comonomers disrupts the regularity and crystalline structure of the nylon 6 molecular chain, leading to a decrease in fiber breaking strength. These problems become more pronounced with increasing sulfonate comonomer content.
[0004] To adjust the molecular weight of copolymer PA6, existing technologies typically use terephthalic acid (TPA), isophthalic acid (IPA), and adipic acid (AA) as end-capping agents. However, for cationic dyeable nylon 6 systems, the chain regularity decreases due to the sulfonate groups, making it difficult for traditional end-capping agents to simultaneously achieve both dyeing performance and mechanical properties.
[0005] Therefore, there is a need to provide a new PA6 copolymer resin and its fiber preparation method, which enables the fiber to be dyed with cationic dyes under normal pressure conditions, while maintaining rheological properties suitable for melt spinning and high breaking strength and elongation at break. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a cationic dyeable nylon 6 copolymer resin and fiber. This method introduces sodium sulfonate-containing copolymer structural units into the nylon 6 molecular chain to provide anionic adsorption sites for cationic dyes, and uses furanoic acid as a molecular weight regulator and end-group introducer, thereby improving the mechanical properties of the copolymerized nylon 6 fiber while achieving cationic dyeability.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing cationic dyeable nylon 6 copolymer resin and fiber, comprising the following steps.
[0008] Step A: Preparation of sodium hexamethylenediamine isophthalate-5-sulfonate (SHS)
[0009] Sodium isophthalic acid-5-sulfonate (SIPNa), hexamethylenediamine (HDA), and deionized water were added to a reaction vessel and stirred at 70–95 °C for 1–3 h, controlling the molar ratio of SIPNa to HDA to be 1:(0.9–1.1) to generate an SHS solution. After the reaction was completed, the solution was purified and dried to obtain solid SHS. The structural formula of the SHS obtained in this step is: .
[0010] Step B: Synthesis of cationic nylon 6 copolymer resin Caprolactam, the SHS obtained in step A, furanoic acid (FA), and water were added to a polymerization reactor to carry out hydrolysis, ring-opening, and polycondensation reactions, yielding cationic nylon 6 copolymer resin chips. In this step, furanoic acid end-capping forms polyamide molecular chains containing furan end groups. The interactions between furan groups include π-π interactions and the formation of dipoles from the amide bonds in nylon. The structural formula is as follows: .
[0011] The raw materials, in molar amounts, are as follows: caprolactam (CPL): 86.8–96.9 mol parts; SHS: 3.0–12.0 mol parts, preferably 3.0–8.0 mol parts, more preferably 5.0 mol parts; FA: 0.1–1.2 mol parts, preferably 0.5–0.8 mol parts; water: 5–15% of the mass of caprolactam.
[0012] The polymerization process is preferably carried out in three stages: (1) Ring-opening stage: 230~250℃, 0.3~1.2 MPa, 2~4 h; (2) Pre-condensation stage: 250~265℃, 0.3~0.6 MPa, 1~2 h; (3) Vacuum condensation stage: 250~270℃, vacuum degree ≤300 Pa, 1~2 h; until the relative viscosity reaches 2.2~3.0 and stabilizes, the material is discharged, water-cooled and pelletized to obtain copolymer resin chips.
[0013] Step C: Melt spinning and drawing
[0014] The chips obtained in step B are vacuum dried at 80-90℃ until the moisture content is ≤200 ppm, and then melt-spun to prepare fibers. The spinning temperature is 245-270℃, the spinneret temperature is 250-275℃, and the draw ratio is 1.5-4.5 times to obtain cationic dyeable nylon 6 fibers. The varieties that can be prepared are POY, FDY and DTY.
[0015] Mechanism of action explanation:
[0016] SHS introduces stable -SO3 into the nylon 6 molecular chain. - Na + The anionic sites can form ionic / hydrogen bonds with cationic dyes for synergistic adsorption, enabling the fibers to achieve high dyeing rates and deep, bright colors at 85–100℃, and also exhibiting high lightfastness.
[0017] This invention uses furanoic acid (FA) as the capping agent, which has the following technical advantages: 1. Planar rigidity and polarity matching: The furan group is an oxygen-containing heteroaromatic structure with higher polarity than the benzene ring, resulting in stronger dipole interaction with the nylon 6 amide segment; 2. π-π stacking reinforcement effect: π-π interactions are formed between furan groups, which is equivalent to building reversible physical cross-linking points, providing additional load-bearing capacity and energy dissipation during stretching; 3. Synergistic effect of rigidity and flexibility: While compensating for the strength loss caused by the introduction of SHS, it can improve toughness and processing stability. Therefore, compared with commonly used TPA, IPA and AA as end-capping agents, FA in the nylon 6 system can not only offset the mechanical loss introduced by sulfonate, but also promote the improvement of elongation and toughness, achieving a performance balance of high strength, high toughness and cationic dyeability. This is a synergistic modification route not reported in the prior art.
[0018] Compared with the closest existing technology, the technical solution provided by the present invention has the following beneficial effects: 1. This invention introduces sodium isophthalate-5-sulfonate, which provides anionic dyeing sites through sodium sulfonate copolymer structural units, enabling fibers to be dyed with cationic dyes under normal pressure conditions of 85-100°C; 2. Considering that the introduction of sulfonate groups would severely disrupt the regularity of the nylon 6 molecular chain, leading to a significant decrease in fiber breaking strength, this invention uses furanoic acid as a capping agent. Through the interaction between furan groups, the crystallization destruction effect caused by sulfonate groups is effectively compensated. By using furanoic acid to adjust the molecular weight and introduce furan end groups, the resulting fiber has higher breaking strength and elongation at break compared to the systems of benzoic acid, terephthalic acid, isophthalic acid, or adipic acid, without significantly reducing dyeing performance and color fastness. 3. This invention optimizes the ratio of SHS to FA to achieve a good balance between dyeing performance, mechanical properties and spinnability. When the SHS dosage is 3.0 to 12.0 moles, the dyeing rate can reach 80% to 95% and the K / S value can reach 25.0 to 39.5. Further optimization shows that when the SHS dosage is 3.0 to 8.0 moles and the FA dosage is 0.3 to 1.0 moles, the fiber breaking strength is maintained at 4.5 to 5.2 cN / dtex and the breaking elongation is 40% to 45%, achieving a good balance between dyeing performance, mechanical properties and spinnability. 4. This invention does not require the introduction of complex esterification pretreatment steps, nor does it require changes to the existing hydrolysis ring-opening polycondensation process of nylon 6. The polymerization and melt spinning processes can be connected with existing nylon 6 production equipment, making it suitable for continuous production. Attached Figure Description
[0019] Figure 1 This is a schematic diagram illustrating the synthesis of the cationic dyeable nylon 6 resin of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The reagents and instruments used in this specific embodiment are all commercially available products.
[0021] Test methods
[0022] 1. Relative viscosity: The sample was prepared into a solution with a concentration of 1.0 g / 100 mL using 96% sulfuric acid as a solvent, and the relative viscosity was measured at 25℃. 2. Mechanical properties: The breaking strength (cN / dtex) and elongation at break (%) were measured according to GB / T 14337. 3. Dyeing performance: Cationic dyes are used for dyeing under normal pressure. The dyeing rate T% and K / S are calculated according to the classical formula. 4. Wash fastness: Assess the degree of color change and staining according to GB / T 3921-2008 (or ISO 105-C10) standard, and take the overall grade; 5. Lightfastness: Grades 1 to 8 are determined according to the xenon lamp method in GB / T 8427-2019.
[0023] Example 1: Preparation of SHS
[0024] 300 g of deionized water was added to a reaction vessel and heated to 80 °C. 50.0 g (0.18 mol) of SIPNa was added and dissolved, followed by the slow addition of 21.0 g (0.18 mol) of hexamethylenediamine. The reaction was maintained at 80 °C for 2 h to obtain an SHS solution. After concentration under reduced pressure, the solution was dried under vacuum at 60 °C for 8 h to obtain a white SHS solid.
[0025] Examples 2-13: Preparation of cationic nylon 6 copolymer chips (gradient ratio)
[0026] According to the formula in Table 1, CPL, SHS, FA and water were added to the polymerization reactor and polymerized in the following three stages: ring-opening stage 230-250℃, 0.6-1.2 MPa, 2-4 h; pre-condensation stage 250-265℃, 0.3-0.6 MPa, 1-2 h; vacuum condensation stage 260-270℃, vacuum ≤300 Pa, 1-2 h; after the viscosity stabilized, the material was discharged, water-cooled and pelletized to obtain copolymer chips.
[0027] The obtained chips had a relative viscosity of 2.35–2.85, a terminal carboxyl group content of 25–35 mmol / kg, and a uniform melt color with no visible gel. Table 1 shows the copolymer chip formulation (molar parts), where E1–E12 correspond to Examples 2–13, respectively.
[0028] Table 1. Copolymer Chip Formulation (Molar Parts)
[0029] Example 14: FDY fiber spinning Select E4 slices from Table 1 and vacuum dry them at 80℃ until the moisture content is 60 ppm.
[0030] Melt spinning conditions: screw 255°C, assembly 260°C, spinneret 48 holes (φ0.25 mm), spinning speed 4300 m / min, draw ratio 1.5. 75 dtex / 48f FDY fibers were obtained. This example demonstrates the specific spinning process for preparing high-strength FDY fibers using the cationic nylon 6 copolymer resin of this invention, proving its good melt stability and spinnability.
[0031] Example 15: Preparation of POY / DTY Fibers
[0032] POY (65 dtex / 24f) was produced by spinning E4 chips from Table 1 at a spinning speed of 4500 m / min, and then DTY was produced by false twisting and texturing (heat box 185℃, D / Y=1.65). This example further demonstrates the process of spinning copolymer resin into POY and then processing it into DTY, indicating that the technology of this invention is suitable for producing textured yarns with good elasticity and rich hand feel, thus broadening the application fields of the products.
[0033] Example 16: Atmospheric Pressure Cationic Staining
[0034] Using E4 fibers from Table 1, cationic red X-GRL or cationic violet X-GRRL were applied. The dye dosage was 2% owf, the liquor ratio was 1:30, the pH was 5.0, and the heating rate was 2... o The dyeing rate was measured at 91% after heating to 90℃ and holding for 90 min, with a K / S ratio of 31.5, a washing fastness of grade 5, a light fastness of grade 6-7, and a bright color.
[0035] Comparative Example
[0036] Comparative Example 1 The amount of SHS is 5.0 mol, and 0.7 mol of TPA is added as a capping agent. The total amount of other raw materials and polymerization and spinning conditions are the same as those for E4.
[0037] Comparative Example 2 The SHS was 5.0 mol parts, and AA was added as a capping agent at 0.7 mol parts. The other conditions were the same as for E4.
[0038] Comparative Example 3 The SHS was 5.0 mol parts, and IPA was added as a capping agent at 0.7 mol parts. The other conditions were the same as for E4.
[0039] Comparative Example 4 The SHS salt was 5.0 mol parts, and benzoic acid (BA) was added as a capping agent at 0.7 mol parts. The other conditions were the same as for E4.
[0040] Comparative Example 5 (Regular Nylon 6) It does not contain SHS, and 0.7 mol of TPA is added as a capping agent. The other conditions are the same as those for E4.
[0041] Comparative Example 6 (Regular Nylon 6) It does not contain SHS, and 0.7 mol of AA is added as a capping agent. The other conditions are the same as those for E4.
[0042] Comparative Example 7 It does not contain SHS, and 0.7 mol of FA is added as a capping agent. The other conditions are the same as those for E4.
[0043] Comparative Example 8 The SHS salt was 1.0 mol, and FA was added as a capping agent at 0.7 mol. The other conditions were the same as for E4.
[0044] Comparative Example 9 The formulation contains 15.0 mol parts of SHS salt and 0.7 mol parts of FA as a capping agent. This formulation is prone to filament breakage during melt spinning, resulting in incomplete fibers and a lack of spinnability.
[0045] Performance test results
[0046] Table 2 Performance of Examples and Comparative Examples
[0047]
[0048] Results Analysis As shown in Tables 2 (E1–E6), with a fixed SHS dosage of 5.0 mol, the FA dosage significantly affects the mechanical properties of the resulting fibers. When the FA dosage increases from 0.1 mol to 0.7 mol, the fiber breaking strength gradually increases from 4.5 cN / dtex to 5.0 cN / dtex, and the breaking elongation increases from 37% to 43%. Simultaneously, the dyeing rate of each sample remains between 90% and 91%, and the K / S value remains between 30.9 and 31.9, indicating that within the above dosage range, changes in FA dosage have no significant effect on the fiber dyeing performance. When the FA dosage further increases to 1.0–1.2 mol, the fiber breaking strength decreases to 4.3–4.7 cN / dtex, and the breaking elongation decreases to 35%–39%. This is because excessive FA may increase the number of end-capped structures in the polymer molecular chain and lead to a decrease in molecular weight, thereby reducing the mechanical properties of the fiber. Therefore, the appropriate amount of FA is 0.3 to 1.0 mol parts, preferably 0.5 to 0.8 mol parts.
[0049] Comparing samples with 5.0 mol of SHS and 0.7 mol of end-capping agent, E4, using FA as a molecular weight regulator and end-group introducer, yielded fibers with a breaking strength of 5.0 cN / dtex, an elongation at break of 43%, a dyeing rate of 91%, a K / S value of 31.5, a washing fastness grade of 5, and a light fastness grade of 6–7. Comparative Examples 1–3, using TPA, AA, and IPA to replace FA respectively, resulted in fibers with breaking strength and elongation at break decreasing to 3.7–3.8 cN / dtex and 32%–34%, respectively, while the dyeing rate remained at 90%–91%, the K / S value at 31.5–32.0, and the washing fastness and light fastness were essentially equivalent to E4. These results indicate that, under the same conditions of SHS and regulator dosage, the introduction of FA has virtually no impact on the cationic dyeing properties imparted by the sodium sulfonate dyeing base, and simultaneously contributes to improving the breaking strength and elongation at break of the fiber.
[0050] Since TPA, AA, and IPA are dicarboxylic acids, while FA is a monocarboxylic acid, their functionalities and the ways in which they regulate molecular chain structure differ during polymerization. Therefore, BA, which is also an aromatic monocarboxylic acid like FA, was selected as a more structurally similar comparison material. Comparing E4 and Comparative Example 4, under the same conditions of SHS dosage and monocarboxylic acid regulator dosage, the breaking strength and elongation at break of FA end-group sample E4 were 5.0 cN / dtex and 43%, respectively, while the breaking strength and elongation at break of BA end-group sample were 4.1 cN / dtex and 34%, respectively. The dyeing rates of both were 91% and 91%, respectively, the K / S values were 31.5 and 31.9, respectively, the washing fastness was grade 5 for both, and the light fastness was grade 6-7 for both. Therefore, compared with BA, which has a similar structure and functionality, FA can increase the fiber breaking strength by approximately 22.0% and the elongation at break by approximately 26.5% while basically maintaining the dyeing rate, color depth, and color fastness. This result indicates that the improvement in the mechanical properties of E4 is not solely due to the use of monocarboxylic acid for end-capping, but is also related to the furan end-group structure introduced by FA.
[0051] The results from E7–E9 and Comparative Examples 8 and 9 show that the amount of SHS has a significant impact on the cationic dyeing performance and melt spinning performance of the fiber. Under the condition of FA dosage of 0.7 mol parts, when the SHS dosage increased from 1.0 mol parts in Comparative Example 8 to 3.0–12.0 mol parts in E7–E9, the fiber dyeing rate increased from 39% to 80%–95%, the K / S value increased from 12.5 to 25.0–45.5, the washing fastness increased from grade 3–4 to grade 4–5 or 5, and the light fastness increased from grade 3–4 to grade 6–7. These results indicate that increasing the SHS dosage can increase the number of sulfonic acid groups in the nylon 6 copolymer, thereby improving the fiber's affinity for cationic dyes, dyeing rate, and apparent color depth.
[0052] However, with the increase of SHS dosage, the breaking strength of the resulting fibers generally showed a downward trend. When the SHS dosage increased from 3.0 mol to 8.0 mol and 12.0 mol, the fiber breaking strength decreased from 5.2 cN / dtex to 4.5 cN / dtex and 4.0 cN / dtex, respectively, indicating that excessive sodium sulfonate copolymer structural units may reduce the regularity of the nylon 6 molecular chain and adversely affect the fiber's crystallization, orientation, and mechanical properties. When the SHS dosage was further increased to 15.0 mol, frequent fiber breakage occurred during melt spinning, and complete fibers could not be obtained continuously and stably, indicating that excessive SHS dosage would also significantly reduce the spinnability of the copolymer resin. Therefore, the appropriate SHS dosage is 3.0–12.0 mol; considering the dye uptake rate of cationic dyes, color depth, mechanical properties, and melt spinning stability, the preferred SHS dosage is 3.0–8.0 mol.
[0053] Comparative Examples 5–7 did not contain SHS. When the resulting fibers were dyed with cationic dyes under the same conditions, the dye uptake was only 13%–16%, and the K / S value was only 4.1–4.2, significantly lower than E7–E9 containing 3.0–12.0 mol of SHS. In particular, although Comparative Example 7 used FA as a molecular weight regulator, its dye uptake was only 15%, and its K / S value was only 4.1, indicating that FA itself cannot impart significant cationic dyeability to nylon 6 fibers; the improvement in fiber dyeing performance mainly comes from the sulfonic acid groups introduced by SHS. On the other hand, the breaking strength of Comparative Example 7 reached 5.5 cN / dtex, while the fiber strength decreased after the introduction of SHS, further indicating that the introduction of SHS has an adverse effect on the mechanical properties of PA6 fibers. Using an appropriate amount of FA in the SHS-containing system helps to compensate for this loss of mechanical properties.
[0054] In summary, SHS is mainly used to introduce sulfonic acid groups into the nylon 6 molecular chain, thereby imparting cationic dyeability to the fiber; FA is mainly used to adjust the molecular weight and end-group structure of the copolymer, and improve the mechanical properties of SHS-containing copolymerized nylon 6 fibers while basically maintaining dyeing performance. FA and SHS work synergistically to achieve a good balance between cationic dyeing performance, mechanical properties, and melt spinning processing performance in the resulting fibers.
[0055] As shown in Table 2, the fiber exhibits better overall performance when the FA dosage is 0.3–1.0 mol and the SHS dosage is 3.0–12.0 mol. Further, the preferred FA dosage is 0.5–0.8 mol and the preferred SHS dosage is 3.0–8.0 mol. Within this preferred range, the representative sample showed a cationic dye uptake rate of 80%–93%, a K / S value of 25.0–39.8, a washing fastness of 4–5 or 5, a light fastness of 6–7, a breaking strength of 4.5–5.2 cN / dtex, and a breaking elongation of 40%–45%. In contrast, the comparative examples 5-7, which do not contain SHS, showed an uptake rate of only 13%–16% and a K / S value of only 4.1–4.2. Therefore, the fiber obtained by this invention can achieve a significantly higher cationic dye uptake rate and color depth value than conventional nylon 6 fiber under normal pressure, and also has good color fastness, mechanical properties and melt spinning processing performance.
[0056] Mechanism verification
[0057] Fibers (FA-terminated) prepared in E4 (corresponding to Example 5) from Table 1 were used as Sample A, and fibers (TPA-terminated) prepared in Comparative Example 1 and fibers (BA-terminated) prepared in Comparative Example 4 were used as Sample C. Dynamic mechanical analysis (DMA) and differential scanning calorimetry (DSC) were performed to verify the reversible physical crosslinking points formed by the π-π interaction between FA groups. DMA was performed in tensile mode at a frequency of 1 Hz, a strain of 0.1%, a heating rate of 3 °C / min, and a test temperature range of 25–180 °C. The storage modulus E' and tanδ were recorded. Simultaneously, a 5% strain loading-unloading cycle (10 times) was performed at 25 °C to determine the elastic recovery rate. DSC was performed under nitrogen protection, with the temperature increased from 25 °C to 250 °C at a rate of 10 °C / min and then decreased. The melting point (T) was recorded. m ) and enthalpy of fusion (ΔH) m ).
[0058] Table 3. Viscosity and DSC results of the samples
[0059] Table 4 DMA test results of the samples
[0060] Table 5 Results of 5% strain cyclic tensile testing
[0061] As shown in Table 3, the relative viscosities of E4, Comparative Example 1, and Comparative Example 4 are 2.49, 2.45, and 2.48, respectively, and the molecular weight difference among the three does not exceed 1.5%. The melting points of E4, Comparative Example 1, and Comparative Example 4 after the second heating are 219.0℃, 218.0℃, and 218.6℃, respectively, and the enthalpy of melting after the second heating are 49.8 J / g, 50.0 J / g, and 50.1 J / g, respectively, indicating that the molecular weight and degree of crystallinity of the three samples are similar.
[0062] As shown in Table 4, the storage modulus of E4 at 100℃ is 1.0 GPa, which is higher than that of Comparative Example 1 and Comparative Example 4 (0.6 GPa and 0.8 GPa, respectively). The storage modulus retention rate of E4 at 100℃ is 40%, compared to 30% and 32% for Comparative Example 1 and Comparative Example 4, respectively. The tanδ main peak temperature of E4 is 63℃, which is 9℃ and 7℃ higher than that of Comparative Example 1 and Comparative Example 4, respectively. These results indicate that the introduction of furan end groups alters the relaxation behavior of the copolymerized nylon 6 segments and improves the modulus retention capacity of the material during heating.
[0063] As shown in Table 5, after 5% strain and 10 load-unload cycles, the residual strain of E4 was 0.42%, lower than that of Comparative Example 1 (0.91%) and Comparative Example 4 (0.74%). The cyclic recovery rate of E4 was 92%, higher than that of Comparative Example 1 and Comparative Example 4 (82%) and Comparative Example 4 (85%). The peak stress retention rate of E4 was 93%, higher than that of Comparative Example 1 and Comparative Example 4 (83%) and Comparative Example 4 (86%). Considering the similar molecular weight and enthalpy of fusion of the three samples, differences in molecular weight and crystallinity can be ruled out as the main reasons for the aforementioned performance differences.
[0064] In summary, without theoretical constraints, the dipole interaction between the furan end groups and the nylon 6 segments, as well as the intermolecular interactions between the furan rings, help to enhance the load transfer between molecular chains and suppress irreversible segment slip during cyclic deformation. This results in E4 exhibiting a high storage modulus retention rate, low cyclic residual strain, and high fracture strength and elongation at break.
[0065] The above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still make modifications or equivalent substitutions to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the protection scope of the claims of the present invention pending approval.
Claims
1. A method for preparing cationic dyeable nylon 6 resin and fiber, characterized in that, Includes the following steps: Step A: Sodium isophthalic acid-5-sulfonate (SIPNa) reacts with hexamethylenediamine (HDA) in an aqueous medium to generate sodium isophthalic acid-5-sulfonate hexamethylenediamine salt (SHS) containing sulfonate groups. Step B: Using caprolactam (CPL), SHS obtained in Step A, furanoic acid (FA), and water as raw materials, a cationic nylon 6 copolymer resin is synthesized through a hydrolysis ring-opening-condensation reaction; Step C: After drying the cationic nylon 6 copolymer resin described in step B, melt spin and draw it to obtain cationic dyeable nylon 6 fiber; Of which, based on a total molar amount of caprolactam, SHS and furanoic acid of 100 parts, caprolactam is 86.8 to 96.9 parts, SHS is 3.0 to 12.0 parts and furanoic acid is 0.1 to 1.2 parts; furanoic acid participates in the polymerization reaction as a molecular weight regulator and end-capping agent.
2. The method for preparing cationic dyeable nylon 6 resin and fiber according to claim 1, characterized in that: The structural formula of sodium hexamethylenediamine isophthalate-5-sulfonate (SHS) is as follows: ; The furanoic acid, after being capped, forms a polyamide molecular chain containing furan end groups. The furan groups interact with each other, and its molecular formula is as follows: 。 3. The method for preparing cationic dyeable nylon 6 resin and fiber according to claim 1, characterized in that: In step A, the molar ratio of sodium isophthalic acid-5-sulfonate to hexamethylenediamine is 1: (0.9-1.1), the reaction temperature is 70-95℃, and the reaction time is 1-3 h.
4. The method for preparing cationic dyeable nylon 6 resin and fiber according to claim 1, characterized in that: In step B, the total molar amount of CPL, SHS, and furanoic acid is 100 parts, with SHS comprising 3.0–8.0 parts and furanoic acid comprising 0.3–1.0 parts. The amount of water added in step B is 5–15% of the caprolactam mass. The hydrolysis ring-opening temperature is 230–250°C, the absolute pressure is 0.3–1.2 MPa, and the reaction time is 2–4 h. The pre-condensation temperature is 250–265°C, the absolute pressure is 0.1–0.6 MPa, and the reaction time is 1–2 h. The vacuum condensation temperature is 250–270°C, the absolute pressure is not higher than 300 Pa, and the reaction time is 1–2 h.
5. The method for preparing cationic dyeable nylon 6 resin and fiber according to claim 4, characterized in that: The SHS is 5.0 parts, and the furanoic acid is 0.5 to 0.8 parts.
6. The method for preparing cationic dyeable nylon 6 resin and fiber according to claim 1, characterized in that: In step C, the melt spinning temperature is 245–270°C, the spinneret temperature is 250–275°C, and the draw ratio is 1.5–4.
5.
7. The cationic dyeable nylon 6 resin prepared by the method for preparing cationic dyeable nylon 6 resin and fiber according to any one of claims 1 to 6.
8. A cationic dyeable nylon 6 fiber prepared by any one of claims 1 to 7, characterized in that: The fiber exhibits a dye uptake rate of ≥80% for cationic dyes at 85–100℃, K / S ≥25, washing fastness ≥4, and light fastness ≥6.
9. The cationic dyeable nylon 6 fiber according to claim 8, characterized in that: Its fracture strength is 4.0–5.2 cN / dtex, and its elongation at break is 28–45%.
10. The cationic dyeable nylon 6 fiber according to claim 9, characterized in that: The fibers are suitable for cationic dyeing of clothing textiles, home textiles and industrial textiles.